The investigation of oncolytic viruses in the field of cancer therapy - Yuan, Zijun; Zhang, Yinping; Wang, Xiang; Wang, Xingyue; Ren, Siqi; He, Xinyu; Su, Jiahong; Zheng, Anfu; Guo, Sipeng; Chen, Yu; Deng, Shuai; Wu, Xu; et al. (Frontiers in Oncology, 2024)
Oncolytic viruses (OVs) have emerged as a potential strategy for tumor treatment due to their ability to selectively replicate in tumor cells, induce apoptosis, and stimulate immune responses. However, the therapeutic efficacy of single OVs is limited by the complexity and immunosuppressive nature of the tumor microenvironment (TME). To overcome these challenges, engineering OVs has become an important research direction. This review focuses on engineering methods and multi-modal combination therapies for OVs aimed at addressing delivery barriers, viral phagocytosis, and antiviral immunity in tumor therapy. The engineering approaches discussed include enhancing in vivo immune response, improving replication efficiency within the tumor cells, enhancing safety profiles, and improving targeting capabilities. In addition, this review describes the potential mechanisms of OVs combined with radiotherapy, chemotherapy, cell therapy and immune checkpoint inhibitors (ICIs), and summarizes the data of ongoing clinical trials. By continuously optimizing engineering strategies